Specifics of digitalization оf the banking sector in Africa ("Journal "U". Economy. Management. Finance.", 2023)
The article presents a look at modern innovation processes in African countries in the field of banking systems. At the current stage of development of technological and financial features in the post-pandemic period, African countries have become more confident in shaping their own agenda in the field of digitalization of finance. This is demonstrated in the form of the growth of regional private business initiatives and cross-regional integration programs in the field of digital finance and banking sector reforms. The purpose of the article is to identify the regional specifics of African digital banking. As a result, a scenario for the possible development of a continent-wide digital banking system is presented.
Keywords: bank; digitalization; finance; payment services; startups; neobanks; mobile banking; microfinance; Africa; Sub-Saharan Africa; megatrends